A Conflict of Interests: A Motivational Perspective on Special Interests and Employment Success of Adults with ASD. - Goldfarb, Yael; Gal, Eynat; Golan, Ofer (Journal of Autism & Developmental Disorders, 2019)
A course of action often suggested in an attempt to improve employment outcomes of adults with autism spectrum disorder, is to match between special interests and job opportunities. In this commentary, we propose that the match may be more complicated than it seems, possibly overseeing more pressing employment needs that should be answered such as: the job's characteristics, labor market demands, and stress resulting from job expectations. Self determination theory of motivation is suggested as a lens through which the association between special interests and a paying job can be examined, highlighting important considerations that hold the potential to increase employment success. Recommendations for new research directions and vocational rehabilitation practice are discussed.